Implementation of LRD (Listen, Read, Discuss) Strategy Learning for Increasing Reading Skill and Student Achievement on Discussion Text Material in Class XII IIK 3 Madrasah Aliyah Negeri 1 Banjarmasin Academic Year 2019/2020 - Mariani Mariani (Jurnal PTK dan Pendidikan, 2019)
Has done research with the aim to increasing reading skill and student achievement on discussion text material through implementation of LRD strategy.  This research design was used classroom action research which consisted two cycles with four phases; planning, action, evaluation and reflection. The subject were 37 students of class XII IIK-3 MAN 1 Banjarmasin. Data collection was used by test technique. Then, data were analyzed by quantitatively and qualitatively techniques. The research result showed that there was an increase in teacher’s activity from 31 at cycle I to 41 at cycle II, an increase in student’s activity from 23,50 at cycle I to 33 at cycle II, an increase in student’s achievement from 64,86 at cycle I to 83,91 at cycle II, an increase in student’s reading skill from 12,23 at cycle I to 15,73 at cycle II and student give good respon for learning which using LRD strategy.